Assessment of Formalin-Fixed Bovine Larynx Asymmetry Using Geometric Morphometry - Arcesio Salamanca-Carreño; Pere M. Parés-Casanova; Mauricio Vélez-Terranova; Néstor Ismael Monroy-Ochoa (The Scientific World Journal)
The vibrations of the larynx produce the voice. Little is known about morphology and the size of cattle larynx. The aim of the study was to quantify the shape asymmetry of the larynx in calves obtained postmortem using a geometric morphometric approach. A sample of 14 larynges from calves (in an age range 335–625 days) belonging to “Bruna dels Pirineus” breed and its F1 crosses was obtained in an abattoir during the first semester of 2021. Laringes were dissected and preserved in the laboratory until their photograph was taken Landmark sets were superimposed on images of fixed transverse sections of larynges. Using geometric morphometric techniques, we analyzed the presence of asymmetries. Asymmetry between sexes was assessed by means of a Canonical Variate Analysis on regression residuals of asymmetric components using the Mahalanobis distance, which assumes a lack of isotropy. Significant differences in the morphometric profile were found between the right and left larynx and between the sexes (p<0.05). Results demonstrate differences between right and left larynx sides as directional asymmetry, at least in fixed structures. Our findings provide a foundation for quantifying the possible contribution of larynx asymmetry among cattle. This study can be considered the first to detect larynx asymmetries in cattle. Studies with a larger sample size are needed to validate the information in large populations. One limitation is that the present study does not have samples from adult animals, so it would be interesting to know if the results are similar among them.